Lincoln's political thought - Kateb, George (Harvard University Press, 2015)
"The book concentrates on Lincoln's political ideas. His speeches, messages, and letters were powerful and concise; they are of lasting theoretical interest and repay close attentive reading. Lincoln's words repay close interpretative reading because he was not always straightforward, and he was unusually complex. The book is about the meanings of his memorable words, especially his Second Inaugural address, and also considers those moments of truth that burst through Lincoln's political caution. In addition, the book takes up Lincoln's troubled justification for unconstitutional constitutionalism, in his unprecedented suspension of the writ of habeas corpus, and examines some reservations toward the claimed military necessity for its justification. Always present in the background was the national crisis over slavery from 1850 to 1865. The book aims to show that Lincoln's success in achieving power came from a deliberate and at times artful moderation"--Provided by publisher